Capacity building of farmers in managing and utilizing local agrarian resources through the dissemination of sustainable farming techniques in Sampuran Village, Muara District, North Tapanuli Regency - Panjaitan, Ade Putera Arif; Telaumbanua, Eben Haezarni; Lumbantobing, Roida; Tindaon, Wensdy; Rajagukguk, Pasu; Saragih, Ratna; Nauly, Meutia; Sinaga, Hotnida; Ayu, Sri Fajar (Talenta Publisher Universitas Sumatera Utara, 2025)
This research focuses on Research and Community Service (PPKM) activities carried out through the collaboration of IAKN Tarutung and USU in the field of agriculture in Sampuran Village, Muara District, North Tapanuli Regency. The primary issue addressed is farmers' complaints about reduced crop productivity caused by plant pests. The main commodities cultivated by the farming community include mango, cacao, avocado, and several types of young plants. The research method used is a qualitative approach with a case study type. The evaluation of the program's impact on farmers' empowerment was conducted using measurable indicators, including the percentage reduction in pest-related damage, changes in crop yields, and the number of farmers adopting pest control techniques introduced during the program. The results show that the Community Service collaboration between IAKN Tarutung and USU contributed significantly to addressing farmers' complaints regarding plant pests. The service was carried out by involving the farming community, facilitated by Sampuran Village officials. Focus Group Discussions (FGDs) with five farmer groups were conducted to identify and address plant pest problems effectively. The program's sustainability strategy includes ongoing training sessions, the establishment of farmer self-help groups, and periodic monitoring facilitated by local agricultural extension officers.